Edukasi Pengajaran Sikap Sopan Santun di Rumah dan Sekolah Sebagai Upaya untuk Meningkatkan Karakter Siswa - Dwi Surya Saputra; Alex Kisanjani; Nadya Novia Rahman (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2024)
Currently, students' social politeness is starting to fade. This is influenced by the development of information technology, cultural modernization and free association. In fact, this attitude is important as a basis for forming a generation of quality and noble character. The aim of this activity is to increase understanding and awareness of the importance of polite culture for elementary school students at SDIT Ma'Arif Sepaku. The method used in this activity is scientific methods of lectures, counseling, training and interactive activities involving students. The results of this work program increase students' understanding of how to interact politely with teachers, parents and peers. Students can also apply the culture of politeness in various situations in everyday life so that they can increase the cultural values of politeness at home and at school.